José Joaquín Camacho and his inluence in the Constitution of the New Provincia of Tunja (1811) - Martínez Garnica, Armando (Universidad Pedagógica y Tecnológica de Colombia, 2012)
José Joaquín Camacho Lago, the citizen of Tunja who was mayor in Pamplona and el Socorro in the irst ten years of the XIXth Century, since 1810 he provided one of the main studies of the irst provincial republics and he used to be the soul of the Congress of the United Provinces of New Granada. His Ibague’s Letters have not been totally assembled and brought together nor re-edited, in spite of the ideological inluence that they had in his time. In this article his ideological inluence distinguishes itself in the text of the Constitution of Republic of Tunja, an act of justice to his name, not recognized because he did not take part personally in the meetings of the electoral and constituent committee.